1997
DOI: 10.1021/ic9609463
|View full text |Cite
|
Sign up to set email alerts
|

Intraligand Charge Transfer in Pt(qol)2. Characterization of Electronic States by High-Resolution Shpol'skii Spectroscopy

Abstract: Pt(qol)(2) (qol(-) = 8-quinolinolato-O,N) is investigated in the Shpol'skii matrices n-heptane, n-octane-h(18), n-octane-d(18), n-nonane, and n-decane, respectively. For the first time, highly resolved triplet phosphorescence as well as triplet and singlet excitation spectra are obtained at T = 1.2 K by site-selective spectroscopy. This permits the detailed characterization of the low-lying singlet and triplet states which are assigned to result mainly from intraligand charge transfer (ILCT) transitions. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 49 publications
8
67
0
Order By: Relevance
“…Because corresponding transitions appear at higher energies for Alq 3 and Rhq 3 (l max 388 and 425 nm respectively), a metal-perturbed, ligand-centered 1 (l 3 p*) (l lone pair/phenoxide) charge-transfer assignment was proposed [15] and later confirmed by Shpol×skii spectroscopic measurements. [19] Because the absorption maxima, bandshape, and intensity of the low-energy bands for Ptq 2 and especially 2 bear great resemblance, we tentatively assign the low-energy absorptions at 400 ± 500 nm in 1 and 2 to a 1 [l 3 p*(diimine)] CT transition mixed with Pt(d) 3 p*(diimine) 1 MLCT. Furthermore, like Ptq 2 , 1 and 2 also display negative solvatochromic shifts (the absorption of 2 at 24 500 cm À1 (408 nm) in C 6 H 6 /CH 2 Cl 2 (10:1) blue-shifts to 26 000 cm À1 (385 nm) in MeOH), and this is consistent with the polar character of the electron-rich oxygen/phenoxide fragment in the ground state.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Because corresponding transitions appear at higher energies for Alq 3 and Rhq 3 (l max 388 and 425 nm respectively), a metal-perturbed, ligand-centered 1 (l 3 p*) (l lone pair/phenoxide) charge-transfer assignment was proposed [15] and later confirmed by Shpol×skii spectroscopic measurements. [19] Because the absorption maxima, bandshape, and intensity of the low-energy bands for Ptq 2 and especially 2 bear great resemblance, we tentatively assign the low-energy absorptions at 400 ± 500 nm in 1 and 2 to a 1 [l 3 p*(diimine)] CT transition mixed with Pt(d) 3 p*(diimine) 1 MLCT. Furthermore, like Ptq 2 , 1 and 2 also display negative solvatochromic shifts (the absorption of 2 at 24 500 cm À1 (408 nm) in C 6 H 6 /CH 2 Cl 2 (10:1) blue-shifts to 26 000 cm À1 (385 nm) in MeOH), and this is consistent with the polar character of the electron-rich oxygen/phenoxide fragment in the ground state.…”
mentioning
confidence: 79%
“…At this juncture, it is appropriate to discuss the photophysical and electronic nature of the closely related bischelate Ptq 2 , which was first investigated in detail by Scandola et al [15] and more recently by Yersin et al [19] In DMF solution, Ptq 2 exhibits a low-energy band at 478 nm (e % 6900 mol À1 dm 3 cm…”
Section: Discussionmentioning
confidence: 99%
“…It is briefly mentioned that the situation for Pt(II) complexes with qol-and qtl-ligands is different, since in these compounds the lowest excited states result from intraligand-charge transfer transitions (3ILCT) with very small metal admixtures [ 195,315,318,319]. This class of compounds exhibits highly efficient red to infrared emissions.…”
Section: Discussionmentioning
confidence: 99%
“…J Resonance-enhanced Raman (RR) modes from [106,211]. protonated guests in comparison to protonated matrices (e.g., see [68,84,195] . It is extremely improbable that all these different dopants are statistically built into this matrix and have exactly the same symmetry and environment as the substituted host cation.…”
Section: Guest Site Symmetries and Environmental Interactionsmentioning
confidence: 99%
“…2 + , with zero-field splittings of the lowest triplet state being 60, [17,18] 76, [28] and 211 cm À1 , [17,18] respectively. In contrast, complexes such as [PdA C H T U N G T R E N N U N G (thpy) 2 ] (thpy = 2-(2'-thienyl)pyridyl), [16,29] [Pd(q) 2 ] (q= 8-quinolinato), and [Pt(q) 2 ], [30] as well as [RhA C H T U N G T R E N N U N G (bpy) 3 ] 3 + [31] and [PtA C H T U N G T R E N N U N G (bpy) 2 ] 2 + [17,18] , are characterized by ZFS values significantly below 1 cm À1 . Thus, it is concluded that these complexes emit only from perturbed ligand-centered triplet states.…”
Section: [L(phenoxide)! P*a C H T U N G T R E N N U N G (Imine)] Andmentioning
confidence: 99%